Biotechnological Applications of Phage and Phage-Derived Proteins - Santos, Sílvio (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Phages have shown a high biotechnological potential with numerous applications. The advent of high-resolution microscopy techniques aligned with omic and molecular tools have revealed innovative phage features and enabled new processes that can be further exploited for biotechnological applications in a wide variety of fields. The high-quality original articles and reviews presented in this Special Issue demonstrate the incredible potential of phages and their derived proteins in a wide range of biotechnological applications for human benefit. Considering the emergence of amazing new available bioengineering tools and the high abundance of phages and the multitude of phage proteins yet to be discovered and studied, we believe that the upcoming years will present us with many more fascinating and new previously unimagined phage-based biotechnological applications.